Strategy In Crisis And Innovation During Pandemic (Case Study Of Abc Hotel In Jakarta) - Ivan Falantti Ishak; Diena M Lemy (Syntax Corporation, 2022)
Impacts of COVID-19 on the global economy and international tourism are disastrous. This pandemic has lasted longer than other previous epidemics, and no single one-time solution could be adopted in the whole period. This research examines those financial impacts during pandemic and how a budget hotel has innovated continuously to sustain economically within a crisis management framework. The data was collected from hotel internal documents and were then discussed in form of interview with the hotel manager. The outcome shows that the pandemic affected differently throughout the period depending on government regulation. During this uncertainty, strategy need to synergize with innovation for flexibility and decision making. Facing exponential decrease in occupancies, process innovation as the driver for cost efficiencies is a must. However, organizational innovations as being able to respond to government actions and applying the right marketing innovations to grab extended stay in accordance with the new operation health and safety protocols are more crucial to achieve economic sustainability in the long run. This critical case study can then help to exemplify even other larger, better equipped, and stronger brand hotels on how to strategize effectively in this pandemic.